Estudo dos níveis salivares de mioinositol e quiroinositol em crianças saudáveis e portadores de diabetes infanto- juvenil - Alves, Karla Shangela da Silva (2012)
Diabetes mellitus is a disease of multiples causes that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces, causing a rise in blood glucose levels (hyperglycemia). It is not clear the action mechanism of insulin but it has been suggested that inositol phosphoglicans, such as myoinositol and D-chiro-inositol, can be important secondary messengers in insulin signal transduction. Although there are some studies linking a reduction in blood glucose levels in diabetic patients with the presence of these inositols in body secretions, there are not reports about the presence of these molecules in salivary composition. Thus, this study aimed to determinate the myoinositol and D-chiro-inositol salivary relation in children with type 1 diabetes and to compare the presence and concentration of these molecules with healthy children (non-diabetic). It has been selected and invited 45 volunteers of both sexes aged 3-12 years, 25 with decompensate type 1 diabetes and 20 healthy children. Saliva samples were collected and centrifuged. The supernatants were separated, purified and lyophilized. The identification of myoinositol and D-chiro-inositol were carried out by means of high-performance liquid chromatography (HPLC). The results showed that children with type 1 diabetes have a lower concentration of D-chiro-inositol and a higher concentration of myoinositol than healthy children. Consequently, the myo/chiro-inositol rate was higher in type 1 diabetes children and there is a correlation between the rate and type 1 diabetes incidence. In conclusion, our data suggests that myoinositol and chiroinositol found in the saliva of children with type 1 diabetes may influence in metabolic control and plays an important role as markers of type 1 diabetes.